The Case for a General Allocation of SDRs During the Tenth Basic Period. (Policy Papers; Policy Paper, 2011)
This paper is the outcome of a periodic process regarding the allocation (or cancellation) of Special Drawing Rights (SDRs), and is a report by the Managing Director to the Board of Governors and the Executive Board along with a staff paper that assesses the merits of a general allocation. Following consultations with the Executive Board on the case for a general allocation, the Managing Director decided not to make a proposal for a general SDR allocation at this time. Though there was openness among many Directors to consider a proposal in the upcoming basic period, there was also a widely-shared sense that it would be premature at this stage, owing to ongoing discussions on the role of the SDR in the context of reform of the international monetary system. Decisions by the Fund on a general allocation or cancellation of SDRs take place at regular intervals (or basic periods) of normally five years, with the Managing Director's report due six months before each new basic period. The tenth basic period begins on January 1, 2012. The report can either propose a general SDR allocation (or cancellation of previous allocations), or conclude that the conditions set out in the IMF's Articles of Agreement for an allocation or cancellation of SDRs are not currently in place, including broad support among IMF members that participate in the SDR Department. Under the IMF's Articles of Agreements, the Managing Director may also propose allocations of SDRs at the request of the Board of Governors or the Executive Board. In this regard, an allocation could be considered if there is a long-term global need for reserves that could be usefully filled at least in part by SDRs and if it would not lead to inflationary pressures, assuming there is broad support among IMF members participating in the SDR Department.